Penerapan Project Based Learning Untuk Meningkatkan Keterampilan Menulis Teks Esai - SIMAN Siman (Jurnal Edutrained : Jurnal Pendidikan dan Pelatihan, 2023)
This study aims to determine the implementation of the Project Based Learning model can improve the skills of writing descriptive essay texts. The subjects of this study were 33 students in class XII IPA3 MAN 1 Sleman in the academic year 2021/2022. The research background is the low ability of students in writing descriptive essay texts. This research was carried out through two cycles, each cycle held two meetings. Data collection techniques used are observation and tests. The instrument used is the teacher's performance observation sheet and student learning activities accompanied by an assessment instrument. While the learning outcomes of students are in the form of descriptive essay text products. The results showed an increase in learning activities using the Project Based Learning model in Cycle I of 22.05% for the high category and in Cycle 2 it reached 44.11% or an increase of 22.06%. Meanwhile, the achievement of teacher performance in cycle I reached 74% and in Cycle 2 reached 85% in the "Good" category, or an increase of 11%. Likewise, the skills of writing descriptive essays have increased. This is illustrated in the increase in the percentage of learning completeness reaching 25%, namely in the first cycle of 63% and in the second cycle reaching 88%